PANDANGAN SARJANA NU TENTANG POSTRADISIONALISME ISLAM - Mahmudah, Siti (ULUL ALBAB Jurnal Studi Islam, 2007)
The objective of this research is to know the ideas and conceptions of NU scholar about â€œpost-tradisionalisme in islamâ€, which is relatively a â€œnewâ€ term. To answer the focus of this research, the writer used qualitative approach, and the techniques used in collecting data were observation, interview, and documentation. While in analyzing the data, the writer used descriptive qualitative analysis. The result of this research is that there are some opinions of NU scholars in East Java about postra. First, postra is considered as a phase of social development. Second, postra is considered as typology of islamic thougth. Postra is one of various kinds or typologies of thought developed in islamic context. Third, Postra is considered as an evaluation of the society. Postra is the reality of progress in islamic thought.